Result of Combined Mifepriston and Misoprostol in Termination of Early Pregnancy at Different Gestational Age (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: An estimated 56 million induced abortion occured each year worldwide. Indirect estimates suggest more than 1.2 million annual menstrual regulations (MRs) and induce abortions each year in Bangladesh. Maternal mortality in Bangladesh is 1.76 /1000 live birth, one fourth of these deaths are due to complication of induced abortion. The safety of procedure is therefore of global public health importance. Now medical abortion option have made more available to women in a variety of health care setting and home administration of medical abortion is acceptable.Objective: To know the outcome and safe use of mifepristone and misoprostol combination up to 9 weeks (